Pengaruh Lalu Lintas Kapal, Pemeriksaan Dokumen, dan Kelaiklautan Kapal terhadap Keselamatan Pelayaran di Pelabuhan Tanjungpinang - Amalia Nur Baeti; Sulistyowati Sulistyowati; Roesjanto Roesjanto (Port Management and Maritime Administration Journal, 2025)
Maritime safety is a fundamental aspect of the sea transportation system and plays a crucial role in supporting the smooth operation of trade, tourism, and community mobility between islands. Ensuring safety is not only dependent on the technical condition of vessels but also on the effectiveness of supervision and operational management at ports. This study aims to analyze the influence of ship traffic, ship document inspection, and vessel seaworthiness on maritime safety at Tanjungpinang Port. The research employed a quantitative approach, with data collected through questionnaires distributed to port officers, ship captains, and crew members, as well as field observations to strengthen empirical findings. The collected data were analyzed using SPSS software through validity tests, reliability tests, and multiple linear regression analysis to determine the relationship and contribution of each variable. The results indicate that all three variables ship traffic, document inspection, and vessel seaworthiness have a positive and significant influence on maritime safety. These findings suggest that proper ship traffic management, orderly administrative inspections, and ensuring that vessels are seaworthy play essential roles in reducing the risk of accidents at sea. This study provides practical implications for port authorities and the Ministry of Transportation, particularly in strengthening supervision systems, improving inspection quality, and enhancing maritime safety management in the Riau Archipelago region, especially at Tanjungpinang Port